INNOVATIVE HAJJ FUND MANAGEMENT TO SUPPORT COST EFFICIENCY THROUGH SEA TRANSPORTATION: A GOVERNANCE STRENGTHENING AND FINANCIAL SUSTAINABILITY MODEL BASED ON DIGITALIZATION - Nopita Sari; Nur Musyahadah (Asian Journal of Islamic Economic Studies, 2026)
The growing interest among Indonesian Muslims in performing Hajj using sea transportation has emerged as a significant trend in recent years. This mode offers a more affordable alternative and has the potential to increase accessibility, particularly for lower-middle-income groups and coastal communities. However, this shift demands innovation in Hajj fund management, which has traditionally focused on conventional schemes and air travel. This study aims to examine how innovations in governance and institutional strengthening of Hajj fund management can support cost efficiency and financial sustainability through the integration of cost-effective sea transportation and service digitalization. A qualitative approach is employed, using a case study of a Hajj fund management institution, supported by literature review and relevant data analysis. The study also incorporates financial modeling to identify potential cost savings and improved liquidity achieved through investment innovation and the digitalization of payment and fund monitoring systems. Findings indicate that integrating sea transportation significantly reduces travel costs and positively impacts budget planning. Key challenges include strengthening institutional governance, enhancing transparency, and implementing real-time digital systems. Technologies such as blockchain and smart contracts have proven effective in increasing public trust and minimizing the risk of fund mismanagement. Furthermore, sustainable investment portfolios aligned with Sharia principles present opportunities to boost income while maintaining long-term financial stability. This research provides both theoretical and practical contributions to the development of an innovative Hajj fund management model that is adaptive to current trends and supports the creation of a transparent, efficient, and sustainable Hajj ecosystem.